ChatGPT, leitura e multiletramentos - França, Carla Maria (2024)
This article is derived from a master’s thesis project in Lexical Studies that belongs to the Programa de Pós-Graduação em Estudo de Linguagens (PPGEL) at the Universidade do Estado da Bahia (UNEB). It is included in the studies of Applied Linguistics (AL) and Text Linguistics (TL) and aims to discuss about the training of teaching and student reading skills in Portuguese, faced with the emergence of chatbots, among which stands out ChatGPT. System or model operated with Artificial Intelligence (IA), ChatGPT can create contents, new and plausible. Through a qualitative document and bibliographic research, we wanted to associate basic concepts such as multiliteracies, textuality, reading and reviewing texts and propositions of the BNCC. This study is justified by the emergence, especially from 2023, of discussions about chatbots and writing in the educational field, supported by the belief that, before each new technology that man employs, it is necessary to rethink basic concepts to deal with the new proposal. It is expected to bring the subject to the field of linguistic studies, and thus to encourage future studies and research that consider languages in their multimodality.